Bioactive Angucyclines/Angucyclinones Discovered from 1965 to 2023 - Hai-Shan Liu; Hui-Ru Chen; Shan-Shan Huang; Zi-Hao Li; Chun-Ying Wang; Hua Zhang (Marine Drugs)
Angucyclines/angucyclinones, a class of polyketides with diverse chemical structures, display various bioactivities including antibacterial or antifungal, anticancer, anti-neuroinflammatory, and anti-α-glucosidase activities. Marine and terrestrial microorganisms have made significant contributions to the discovery of bioactive angucyclines/angucyclinones. This review covers 283 bioactive angucyclines/angucyclinones discovered from 1965 to 2023, and the emphasis is on the biological origins, chemical structures, and biological activities of these interesting natural products.